Enhancing Biology Students' Scientific Literacy through the Critical Analysis and Discussion-Comparison with the Extended Learning Community Model - Irwandi, Irwandi; Ade Cahaya, Mariana; Syahfitri, Jayanti; Waluyo, Budi; Arsyad, Safnil (Jurnal Pendidikan IPA Indonesia, 2025)
Despite global reforms in science education that emphasize collaboration, critical thinking, and real-world application, many secondary students continue to struggle with scientific reasoning and communication, particularly in Biology. This study addresses this gap by evaluating the effectiveness of the Critical Analysis and Discussion Comparison with Extended Learning Community (CADC-ELC) method in enhancing students' written and oral communication and cognitive performance. Employing a quasi-experimental design with 90 tenth-grade students in Indonesia, participants were divided into three groups: CADC-ELC, CADC-only, and conventional instruction. Data were collected using validated observation sheets and a 30-item cognitive test and analyzed using the Games-Howell post-hoc test. Results revealed that CADC-ELC significantly outperformed other groups in all areas: written communication improved from M = 31.0 to 70.3, oral communication from M = 9.1 to 17.06, and cognitive scores from M = 33.3 to 83.1 (all p < .001). These findings suggest that CADC-ELC offers a robust, globally relevant model for strengthening science education through dialogic, scaffolded, and context-rich instruction.